Staged surgical management and its impact on quality of life for stage 3 hidradenitis suppurativa in adolescents - Julia M. Power; Anne F. Faulk; India Hill; Jessica A. Zagory (Elsevier, 2024)
Background: Hidradenitis suppurativa (HS) can present significant physical, psychological, social, and financial burden. Here, we describe surgical and quality of life outcomes for adolescent patients with axillary Hurley stage 3 HS who underwent staged surgical management. Methods: We performed a single-center, retrospective review of patients ≤21 years who had axillary Hurley stage 3 HS. A standardized, staged surgical approach was implemented. Primary outcomes were length of stay, length of negative pressure wound therapy (NPWT) use, number of operations, range of motion, and graft uptake. Secondary outcome was depression, suicidal ideation, and social changes including return to school or work. Results: Nine adolescent female patients with axillary Hurley stage 3 HS were included, of whom 6 underwent surgery (9 total sites) and 3 remained on medical therapy. Patients had 6.5 ± 4.6 visits to the emergency department prior to surgery referral and had undergone 7.5 ± 5.1 incision and drainage procedures. For patients undergoing surgical management, NPWT duration was 23 ± 4 days, with 2-3 NPWT changes. Graft uptake was 80-100 % with 100 % return of full range of motion. No disease recurrence has been noted. All patients undergoing surgical management reported improvement in depression and suicidal ideation. Conclusion: Well-defined staged surgical approach for axillary Hurley stage 3 HS can offer adolescent patients disease eradication, improvement in range of motion, and improvement in quality of life. Study type: Retrospective review, case series. Level of evidence: IV.